Keeping youth in the community through an intensive case management and family partnerships model. Issue 1 (1st January 2022) - Winokur, Marc; Orsi, Rebecca; Chen, Pang Ching Bobby; Alessi, Lauren
ABSTRACT: The Family Partnerships Program (FPP) is an intensive case management model that serves families with child welfare and juvenile justice involved youth who are at imminent risk of out-of-home placement. FPP is based on the belief that relationships, both with families and across systems, is foundational when supporting change with youth. Propensity score matching was utilized to determine if FPP is related to improved child welfare re-involvement outcomes when compared with treatment as usual for this population. When compared to non-FPP youth in two comparison counties, FPP youth from Larimer County, Colorado experienced 51% lower odds of juvenile justice involvement at case closure compared to remaining home, 32% lower odds of runaway/emancipation compared to remaining home, and 74% lower odds of placement compared to remaining home. When comparing a group of youth from Larimer County who did not receive FPP to youth in the comparison counties, the results are similar. Although this effect does not appear to be isolated to FPP; one possibility is that intensive case management represents an "active ingredient" of what makes Larimer County's community-based approach viable for serving the crossover youth population. Implications for program and policy development and directions for future research are discussed.